PREVALENSI PENYAKIT PADA KARANG KERAS DI PERAIRAN KALEDUPA, TAMAN NASIONAL WAKATOBI - Ainul Rahman; Nor Sa'adah; Nirmalasari I. Wijaya; Ardhi Syam Bahroun (Universitas Hang Tuah, 2021)
Coral disease is a disturbance to coral health that causes physiological disturbances for coral biota. The emergence of coral disease is characterized by discoloration, damage to skeleton coral biota, to the loss of its tissueThis study aims to identify the type of coral disease and determine its prevalence in Kaledupa Waters, Wakatobi National Park, Southeast Sulawesi. This research was conducted in June 2021 in the Kaledupa Waters of Wakatobi National Park using the Belt Transect method with a size of 3 x 50 m at 3 observation points at a depth of 3-5 meters. Measurement of Oceanographic Physics-Chemistry parameters is carried out directly in the field. Identification of coral diseases was carried out descriptively based on the coral disease handbook and journal references. The results obtained found 4 types of coral disease that infect coral biota in the waters of Kaledupa Island, Wakatobi National Park, namely Black Band Disease (BBD), White Band Disease (WBD), White Pox and Ulcerative White Spot (UWS). As well as the results obtained for the overall prevalence of coral disease in the study site an average of 1.5%.